Zambia building prosperity from resource wealth - edited by Christopher S. Adam (Oxford Oxford University Press, 2014)
Zambia is a landlocked mineral dependent country in Southern Africa whose history is intimately entwined with the copper mining industry. Having gained Independence from Britain in 1964 at the height of a copper boom, the country experienced a slow and painful economic decline over the next quarter century. However, following a traumatic and protracted process of economic adjustment through the 1990s and early 2000s, Zambias economic potential is now better than ithas been at any time since Independence. This book, which contains a set of rigorous but accessible essays by a range of Zambian and international scholars, seeks to examine the challenges and opportunities that currently face Zambian policymakers as they seek to harness the countrys valuable natural assets to broad-based and sustainable economic growth over the coming decades. Written in a non-technical manner by leading scholars in the field, the chapters address key challenges in the areas of natural resource management,agriculture, trade, employment and migration, education, finance, and investment. This is the second volume in the Africa: Policies for Prosperity series following on from the successful first volume on Kenya.
Includes bibliographical references and index.
Keywords: Economic development--Zambia. Natural resources--Zambia. Zambia--Economic policy. Zambia--Economic conditions